2002
DOI: 10.1074/jbc.m110650200
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sterol Regulatory Element-binding Protein 1 in Regulation of Renal Lipid Metabolism and Glomerulosclerosis in Diabetes Mellitus

Abstract: Diabetic renal disease is associated with lipid deposits in the kidney. The purpose of our study was to determine whether there is altered regulation of the sterol regulatory element-binding proteins (SREBPs) in the diabetic kidney and whether SREBPs mediate the abnormal renal lipid metabolism and diabetic renal disease. In streptozotocin-induced diabetes in the rat, there were marked increases in SREBP-1 and fatty acid synthase (FAS) expression, resulting in increased triglyceride (TG) accumulation. Treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
262
1
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 298 publications
(278 citation statements)
references
References 41 publications
12
262
1
3
Order By: Relevance
“…29,30 Overexpressing the active form of SREBP-1 in the kidneys of mice induces proteinuria. 31 Our results suggest, for the first time, that activation of SREPBs and accumulation of lipids within the kidney also occur in LN.…”
Section: Discussionmentioning
confidence: 76%
“…29,30 Overexpressing the active form of SREBP-1 in the kidneys of mice induces proteinuria. 31 Our results suggest, for the first time, that activation of SREPBs and accumulation of lipids within the kidney also occur in LN.…”
Section: Discussionmentioning
confidence: 76%
“…These changes were consistent with the effects of aging and CR on the expression of nuclear SREBP-1 and SREBP-2. In the SREBP-1a transgenic mouse, we have found increased renal expression of TGF-␤ and VEGF as well as increased expression of type IV collagen and fibronectin, well-established mediators of glomerulosclerosis and proteinuria (19). In addition, cell culture studies have shown that in mesangial cells, LDL or VLDL induces upregulation of TGF-␤ and PAI-1 and accumulation of ECM proteins (40 -42).…”
Section: Role Of Altered Lipid Metabolism In Renal Diseasementioning
confidence: 93%
“…We reported previously that in SREBP-1a transgenic mice overexpressing SREBP-1 in kidney, in the absence of any increases in serum glucose, triglyceride, or cholesterol, there were increased renal triglyceride accumulation and upregulation of TGF-␤ and VEGF, resulting in accumulation of fibronectin and type IV collagen, glomerulosclerosis, and proteinuria (19). Therefore, our main purpose in this study was to determine whether the effects of CR are mediated at least in part by the modulation of renal lipid metabolism.…”
Section: Cr Prevents Age-related Increase In Lipid Accumulation and Imentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it was recently reported that the CRE at −177 in the mouse HKα2 promoter played a functional role in regulating gene expression [23]. Similarly, NF-κB inhibits transcription of HKα2 in a mouse medullary collecting duct cell line [24]; a putative NF-κB site is located at −486 in the rabbit HKα2 promoter.…”
Section: Discussionmentioning
confidence: 99%